Proteomics in Biology. - Shukla, Arun K. (Methods in enzymology, 2017)
Proteomics in Biology, Part B, the latest volume in the Methods in Enzymology series, continues the legacy of this premier serial with quality chapters authored by leaders in the field. This volume covers research methods in proteomics.